Evaluation of an Intervention Instructional Program to Facilitate Understanding of Basic Particle Concepts Among Students Enrolled in Several Levels of Study - Treagust, David; Chandrasegaran, A.; Zain, A.; Ong, E.; Karpudewan, M.; Halim, L. (The Royal Society of Chemistry, University of Ioannina, 2011)
The efficacy of an intervention instructional program was evaluated to facilitate understanding of particle theory concepts among students (N = 190) using a diagnostic instrument consisting of eleven two-tier multiple-choice items in a pre-test – post-test design. The students involved were high school students, undergraduates and postgraduates from six educational levels. The eleven items evaluated understanding in three key conceptual categories: (1) intermolecular spacing in matter, (2) the influence of intermolecular forces on changes of state and (3) diffusion in liquids and gases. The intervention program proved effective in improving students' overall understanding of particle theory concepts, with statistically significant improvement in overall scores among students in five of the six groups. However, only 25-46% of the students displayed consistent understanding of the concepts in the three conceptual categories.